2004
DOI: 10.1016/j.ejvs.2003.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Endovascular and Open AAA Repair. Results of a Randomised Triala

Abstract: In the early postoperative period there is a small, yet significant QoL advantage for EVAR compared to OR. At 6 months and beyond, patients reported better QoL after OR than after EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
120
2
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 17 publications
7
120
2
3
Order By: Relevance
“…The conclusions we have drawn are based on a small number of subjects, however the number of subjects included in the study are similar to previously published studies [4][5][6][7][8][9][10].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The conclusions we have drawn are based on a small number of subjects, however the number of subjects included in the study are similar to previously published studies [4][5][6][7][8][9][10].…”
Section: Discussionsupporting
confidence: 73%
“…Several studies have shown that shortly after the operation OR patients have a poorer HRQoL in several domains compared to EVAR patients [4][5][6][7][8][9][10]. In the present study overall NHP showed a significant decreased in HRQoL in the OR groups but not in EVAR group at one month.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The ultimate decision regarding which type of repair should be used in a given patient with an abdominal aortic aneurysm is based on a number of factors, including the quality of life expected postoperatively, cost-effectiveness, risk of sexual dysfunction, risk of aneurysm rupture, and reintervention rate. 29 These factors must be considered before a final decision is reached. Our results indicate that in patients who are candidates for both techniques, endovascular repair is preferable to open repair, given its lower rates of operative mor-n engl j med 351;16 www.nejm.org october 14 , 2004 The new england journal of medicine 1616 * The standards of the Society for Vascular Surgery/International Society for Cardiovascular Surgery were used.…”
mentioning
confidence: 99%